The effect of temperature, incubation and storage time on lactic acid content, pH and viscosity of goat milk kefir - Yola Desnera Putri; Nur Asni Setiani; Sohadi Warya (Institut Teknologi Bandung, 2020)
Kefir is a fermented beverage that has probiotic properties and often used as a cosmetic or ointment raw material. Its lactic acid content is classified as AHA (alpha hydroxy acid) which is known good for skin health. The objectives were to study the influence of temperature, fermentation and storage time on the amount of lactic acid, pH and viscosity of kefir. Fermentation of kefir was performed at two different temperatures (room temperature and 37oC) for 24 and 48 h. Storage condition of kefir products was performed at cold and room temperature for 4 to 28 d. The content of lactic acid was based on the total organic acid determined using acid-base titration. The results showed that the average content of lactic acid in 48 h-fermented kefir at room temperature and 37oC were 0.9 to 2.2% with pH and viscosity characteristics were 4.1 to 4.3 and 1400 to1600 cPs, respectively. Meanwhile, during 24 d of storage, the average content of lactic acid was 1.97 to 3.54%, where pH and viscosity characteristics were 3.5 to 4.5 and 3400 to 6400 cPs, respectively. The optimum storage time of goat milk kefir is obtained on days 4 to 12 and they can be stored for up to 24 days without deterioration of kefir products.